Assessing the impacts of various street-level characteristics on the burden of urban burglary in Kaduna, Nigeria. (January 2020) - Musah, Anwar; Umar, Faisal; Yakubu, Khadijat N.; Ahmad, Muktar; Babagana, Abdullah; Ahmed, Adamu; Thieme, Tatiana A.; Cheshire, James A.
Abstract: Evidence suggests that crimes committed in urban environments are geographically concentrated across a range of scales, and that the variation in rates of crime within an urban space is significantly dependent on the physical environment as well as the situation in which the crime takes place. However, these assertions are typically drawn from environmental criminological studies that have focussed on Euro-American cities and western intellectual perspectives. We seek to move beyond these by focussing on a second-tier city in sub-Saharan Africa (Kaduna, Nigeria), a context for which very little literature exists. This paper therefore examines the association between a range of street characteristics and the risk of residential burglary in Kaduna for the first time. It describes a methodology for conducting a household crime victimisation survey in Nigeria, and then aggregating the information to a street-level to perform a population-based ecological study. It integrates street network analysis and statistical modelling techniques in order to provide novel estimates for factors that may increase the risk of burglary such as street accessibility metrics (e.g. connectivity, betweenness and closeness centrality), segment length, socioeconomic status and business activities. Finally, the article provides a discussion on the plausibility and implication of findings within the sub-Saharan African context.